TELLURIDES IN ORE MANIFESTATIONS OF GOLD – ARSENIC TYPE OF WESTERN PART OF THE UKRAINIAN SHIELD - HRINCHENKO, O.; BONDARENKO, S.; SOMKA, V.; BONDARENKO, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2005)
This article presents the preliminary data concerning distribution and features of tellurides formation in ore manifestations of gold – arsenic type at the western part of the Ukrainian Shield. according to data obtained almost full domination of compounds with bismuth is observed among tellurides. There are also observed certain regional zonality in distribution of tellurides within the limits of western and east frames of magmatic system of Korsun'-Novomirgorodsky pluton – Novoukrainsky massif.